Experimental Research on Vibrating Effect for Absorption Refrigeration - Shen Jiang; Dong Bin; Josephine Lau; Shen Ziqi; Wang Jianmin (Zhileng xuebao)
Lithium bromide absorption refrigeration testing with an electric vibrating system was established. Making use of the testing, performance of major parts of LiBr absorption chiller is analyzed. The main purpose is to analyze the effect of vibration on the performance of heat transfer and cooling during absorption refrigeration. The results indicate that compared with static conditions, the heat transfer property of the absorber and the evaporator has a better performance under vibrating conditions. The vibration contributes to heat transfer enhancement, increases refrigerating capacity and improves the COP.